Dynamic changes in intestinal microbiota and metabolite composition of pre-weaned beef calves. (February 2023) - Liu, Hongye; Yan, Chunri; Hao, Chunyun; Wang, Danqi; Liu, Yize; Luo, Zhao-Bo; Han, Sheng-Zhong; Wang, Jun-Xia; Li, Dongxu; Zhu, Jun; Chang, Shuang-Yan; Yang, Liu-Hui; et al.
Abstract: Gut microbes and their metabolites are essential for maintaining host health and production. The intestinal microflora of pre-weaned calves gradually tends to mature with growth and development and has high plasticity, but few studies have explored the dynamic changes of intestinal microbiota and metabolites in pre-weaned beef calves. In this study, we tracked the dynamics of faecal microbiota in 13 new-born calves by 16S rRNA gene sequencing and analysed changes in faecal amino acid levels using metabolomics. Calves were divided into the relatively high average daily gain group (HA) and the relatively low average daily gain group (LA) for comparison. The results demonstrated that the alpha diversity of the faecal microbiota increased with calf growth and development. The abundance of Porphyromonadaceae bacterium DJF B175 increased in the HA group, while that of Lactobacillus reuteri decreased. The results of the LEfSe analysis showed that the microbiota of faeces of HA calves at eight weeks of age was enriched with P. bacterium DJF B175, while Escherichia coli and L. reuteri were enriched in the microbiota of faeces of LA calves. Besides, the total amino acid concentration decreased significantly in the eighth week compared with that in the first week ( P  < 0.05). Overall, even under the same management conditions, microorganisms and their metabolites interact to play different dynamic regulatory roles. Our results provide new insights into changes in the gut microbiota and metabolites of pre-weaned calves. Highlights: The faecal microbiota flora of pre-weaned calves changed significantly with growth. The composition of the faecal flora was different for calves with different ADG. Faecal amino acid levels were significantly lower in calves at weaning than at birth.